Thrombophlebitis of the Right Renal Capsular Vein during the Early Postpartum Period - Koji Nakamura; Kensuke Nakanishi; Satoshi Kubota; Ryoko Takahashi; Mari Tomiie; Akihiro Moriyama (Hindawi Limited, 2018)
Venous thrombophlebitis is an uncommon cause of fever and lower abdominal pain during the early postpartum period. It mostly occurs in the right ovarian vein, and computed tomography (CT) is useful for diagnosis. We present a case of thrombophlebitis of the renal capsular vein. A 27-year-old postpartum woman presented with right lower abdominal pain and fever unresponsive to antibiotics. Contrast CT showed a ring-enhancing mass in the right retroperitoneum, which was distinct from the right ovarian vein. Exploratory laparoscopy revealed a retroperitoneal hematoma and normal appendix. Reconstruction of CT images revealed that the mass was connected to the right renal capsular vein. Anticoagulation therapy improved the patient's symptoms. Postpartum thrombophlebitis can occur at locations other than the ovarian vein, such as the renal capsular vein. If a retroperitoneal mass is discovered during puerperium, a thorough investigation of the mass's continuity with surrounding vessels is essential to avoid unnecessary surgery.